Pengaruh Variasi Suhu Pada Proses Tempering dan Hardening Dengan Media Pendingin Oli Terhadap Kekuatan Tarik As Baja Dan Kuningan - Darwis Darwis (Celebes Engineering Journal, 2020)
The aim of this research is the effect of heat treatment on steel axles and brass on the tensile strength using cooling media. Tests were conducted to determine the strength of materials such as tensile testing and materials used in the testing are as steel and brass. The strength achieved depends on the heating temperature, holding time and cooling rate in the heat treatment. In the process of Tempering used temperature 500°C with holding time 60 minutes, while in Hardening with temperature 850°C with holding time 30 minutes. Through the tensile test results obtained by the average value results in tempering the tensile strength of steel as σu maximum of 49.76 kg/mm2, while hardening the maximum tensile strength as brass that is 46.58 kg/mm2. At 850°C hardening of steel axles the maximum tensile strength 42.03 kg/mm2, while the brass axes with maximum tensile strength σu 49.68 kg/mm2, whereas without heat treatment the tensile strength strength of steel axes σu 152.03 kg/mm2, and brass axle σu 50.65 kg/mm2. From the results obtained the highest value on the steel axes without heat treatment while the lowest value of the maximum strength obtained at tempering with the maximum stress of the steel axle.